1989
DOI: 10.1002/cne.902870204
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of substance P‐ and neurokinin A‐encoding preprotachykinin mRna in the female rat brain

Abstract: To determine the locations of neurons in the rat brain expressing substance P and neurokinin A mRNA, we performed in situ hybridization with a radiolabeled cRNA probe that was complementary to alpha-, beta-, and gamma-preprotachykinin mRNA. Several types of controls indicated specificity of the labeling. Brain regions containing many labeled neurons include the anterior olfactory nucleus, layer II of the olfactory tubercle, the islands of Calleja, the nucleus accumbens, the caudate-putamen, portions of the amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
43
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 113 publications
13
43
1
Order By: Relevance
“…In addition, the majority were positive for dynorphin but negative for enkephalin. Previous studies have shown that the ICjM contains substance P (Beckstead and Kersey 1985;Gerfen and Young 1988;Harlan et al 1989). This suggests that ICjM neurons contain both dynorphin and substance P as is the case for some medium spiny neurons in the dorsal striatum.…”
Section: Phenotypes Of Clozapine-induced Fos-positive Neuronsmentioning
confidence: 99%
“…In addition, the majority were positive for dynorphin but negative for enkephalin. Previous studies have shown that the ICjM contains substance P (Beckstead and Kersey 1985;Gerfen and Young 1988;Harlan et al 1989). This suggests that ICjM neurons contain both dynorphin and substance P as is the case for some medium spiny neurons in the dorsal striatum.…”
Section: Phenotypes Of Clozapine-induced Fos-positive Neuronsmentioning
confidence: 99%
“…SP, NKA and NKB bind preferentially to the NK1, NK2 and NK3 receptor, respectively [26], but each of these three neuropeptides is capable of eliciting responses from all three neurokinin receptors [27]. Our recent study showed that oral administration of an antagonist for all three neurokinin receptors (NK1, NK2 and NK3 receptors) has testicular toxicity through inhibition of gonadotropin secretion in dogs [28], suggesting that the reproductive toxicity of the antagonist might be associated with the mechanism of GnRH pulse generation.Tac1 (gene encoding SP, NKA, NPK and NPγ) and Tac2 (gene encoding NKB) mRNA-expressing neurons are located in several hypothalamic nuclei such as the medial preoptic area and ARC in rats [29,30]. SP or NPK neurons project their fibers to hypothalamic areas such as the medial preoptic area [31,32], paraventricular nucleus [33] and ARC in rats [34].…”
mentioning
confidence: 99%
“…Tac1 (gene encoding SP, NKA, NPK and NPγ) and Tac2 (gene encoding NKB) mRNA-expressing neurons are located in several hypothalamic nuclei such as the medial preoptic area and ARC in rats [29,30]. SP or NPK neurons project their fibers to hypothalamic areas such as the medial preoptic area [31,32], paraventricular nucleus [33] and ARC in rats [34].…”
mentioning
confidence: 99%
“…For example, substance P is synthesized in nociceptive primary sensory neurons, which send C-and A␦ fibers to dorsal horn projection neurons in lamina I and IV-V, and to nociceptionspecific interneurons in lamina II-III of the spinal cord. Axons of projection neurons terminate in many supraspinal nuclei that are involved in pain transmission (10,11). Nociceptive stimulation triggers the release of substance P from C-afferent terminals in the marginal layers of the spinal cord (12), evokes slow excitatory postsynaptic potentials in second-order sensory neurons in the dorsal horn, and facilitates their activation (13).…”
mentioning
confidence: 99%